2007
DOI: 10.2500/ajr.2007.21.2961
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Nasal Septal Deviation and its Surgery on Nasal Mucociliary Clearance in Both Nasal Cavities

Abstract: The results of this study showed that NSD significantly impaired NMCVs in both sides and that septoplasty significantly improved NMCVs in both sides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
1
18
0
2
Order By: Relevance
“…NSD negatively affects the MCA, likely due to loss of cilia, increased inflammation, and decreased density of glandular acini [11]. Following a septoplasty, impairment of the MCA is improved with time [8, 9, 16]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NSD negatively affects the MCA, likely due to loss of cilia, increased inflammation, and decreased density of glandular acini [11]. Following a septoplasty, impairment of the MCA is improved with time [8, 9, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…In review of studies using rhinoscintigraphy in the most recent 14 years [5, 7, 9, 17, 2123], we have seen that the average NMTRs of healthy individuals range between 4.48 and 17.94 mm/min (mean 8.92 mm/min). In all of these studies, individual NMTRs range between 1.2 and 28.7 mm/min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coste et al [14] observed that the radiofrequency thermal ablation surgery have preserved the nasal mucociliary functions after only one application. Ulusoy et al [15] observed that before the septal surgery, the nasal mucociliary clearance velocity (NMCV) of concave (10.24 ± 3.96 mm/ min) and convex sides (10.78 ± 3.53 mm/min) of the patients were significantly lower than the control group (17.94 ± 2.89 mm/min). They determined no statistically significant difference between the NMCV of the concave and convex sides.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism for this occurrence is not understood, but previous investigators have also reported more prominent infiltration of inflammatory cells in the less ventilated nasal cavity [2]. In patients with deviated nasal septum the concave nasal cavity has impaired mucociliary transport and increased inflammation in comparison with the convex nasal cavity [2Á4] and the status after septoplasty [5]. The results suggest that association of hypoventilation and rhinosinusitis is not so clear.…”
Section: Discussionmentioning
confidence: 79%